2016
DOI: 10.3389/fmed.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Combination Treatment Using Palonosetron, Promethazine, and Dexamethasone on the Prophylaxis of Postoperative Nausea and Vomiting and QTc Interval Duration in Patients Undergoing Craniotomy under General Anesthesia: A Pilot Study

Abstract: IntroductionPostoperative nausea and vomiting (PONV) is a displeasing experience that distresses surgical patients during the first 24 h after a surgical procedure. The incidence of postoperative nausea occurs in about 50%, the incidence of postoperative vomiting is about 30%, and in high-risk patients, the PONV rate could be as high as 80%. Therefore, the study design of this single arm, non-randomized, pilot study assessed the efficacy and safety profile of a triple therapy combination with palonosetron, dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
(63 reference statements)
3
12
0
Order By: Relevance
“… 26 The use of promethazine in the craniotomy population should also be considered cautiously when immediate postoperative neurological evaluation is required because of its potential sedating effect. 1 , 25 The results of the aforementioned trials using triple therapy are consistent in reporting significantly lower rates of PONV following craniotomy when compared with previously published data. 7 15 , 17 21 , 25 , 26 …”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“… 26 The use of promethazine in the craniotomy population should also be considered cautiously when immediate postoperative neurological evaluation is required because of its potential sedating effect. 1 , 25 The results of the aforementioned trials using triple therapy are consistent in reporting significantly lower rates of PONV following craniotomy when compared with previously published data. 7 15 , 17 21 , 25 , 26 …”
Section: Resultssupporting
confidence: 74%
“… 1 , 22 , 62 Furthermore, in a single-arm study using a triple therapy of palonosetron (0.075 mg), dexamethasone (10 mg), and promethazine (25 mg) we reported a 30% incidence of PON and 7.5% incidence of PONV after craniotomy, without evidence of QT interval prolongation, a common adverse effect associated with palonosetron use. 25 Last, an RCT conducted by our group found that the combination of intravenous promethazine (25 mg) and dexamethasone (10 mg) with oral aprepitant (40 mg) had similar efficacy in the prevention of PONV to intravenous promethazine (25 mg), dexamethasone (10 mg) and ondansetron (4 mg) (PONV rates of 31% and 36.2%, respectively). 26 The use of promethazine in the craniotomy population should also be considered cautiously when immediate postoperative neurological evaluation is required because of its potential sedating effect.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, fungal infections with Aspergillus fumigatus and Cryptococcus neoformans can be acquired from non–endogenous host surroundings ( Badiee and Hashemizadeh 2014 ). Infections in patients with severe immunological impairment can have fatal consequences due to the development of resistance by these fungi to the limited number of therapeutic antifungal drugs currently available ( Roemer and Krysan 2014 ; Sanglard 2016 ). Therefore, there is an urgent need for new therapeutic strategies to address drug resistance in fungal infections.…”
mentioning
confidence: 99%
“…1,2 Post-operative nausea and vomiting can be classified as either early PONV (0-2 hours) or delayed PONV (2-24 hours). 3 PONV has a complex and multifactorial aetiology, but there are a number of recognised contributing factors. These include patient, anaesthetic, surgical and postoperative conditions.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%